A METHODOLOGICAL CONTRIBUTION TO MEASURING SKILL (MIS)MATCH*. (19th June 2012) - SGOBBI, FRANCESCA; SULEMAN, FÁTIMA
<x xml:space="preserve">Abstract</x> Researchers have long expressed their discontent with the existing measures of skill mismatch. This paper argues that traditional measures cannot fully capture the essence of an inherently multidimensional and job‐specific concept such as skill mismatch. An empirical job‐based methodology is proposed that classifies the types of skill (mis)matches based on performance of core skills and supplementary skills. The proposed methodology is tested on a sample of 600 Portuguese retail bankers. The results support the job‐specific nature of skills. The differentiated distribution of skill (mis)match by job is a significant determinant of earnings among the sampled retail bankers.